Aluminum alloy chemical zinc deposition agent and zinc deposition method

By adjusting the type and dosage of zinc salt, controlling the dosage ratio of complexing agent and stabilizer, and adjusting the temperature and time of zinc sedimentation, a chemical zinc sedimentation agent of aluminum alloy was prepared, which solved the problems of poor bonding ability of the zinc sedimentation layer and the aluminum alloy matrix and poor corrosion resistance, and achieved the effect of improving the zinc deposition rate and layer thickness, enhancing the binding force and corrosion resistance.

CN119243133BActive Publication Date: 2025-03-11LANGXI COUNTY KEHONG CHEM CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411799321.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-09
Publication Date
2025-03-11
Estimated Expiration
2044-12-09

AI Technical Summary

Technical Problem

The existing aluminum alloy zinc-dip agents have problems such as poor bonding ability of the zinc-dip layer and poor corrosion resistance and common acidic zinc-dip method reduces the practicality of the aluminum alloy.

Method used

By adjusting the type and dosage of zinc salt, controlling the dosage ratio of complexing agent and stabilizer, adjusting the temperature and time of zinc sedimentation, and using a mixed solvent of methanol and water, a chemical zinc sedimentation agent of aluminum alloy was prepared to improve the zinc deposition rate and layer thickness, and enhance the binding force and corrosion resistance of the zinc sedimentation layer and the aluminum alloy matrix.

Benefits of technology

It has achieved the improvement of zinc deposition rate and layer thickness, enhanced the bonding force and corrosion resistance of the zinc deposited layer and aluminum alloy matrix, and improved the application range and practicality of aluminum alloy.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119243133B_ABST
    Figure CN119243133B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of metal material surface treatment, specifically to a chemical zinc deposition agent and zinc deposition method for aluminum alloy. The present invention overcomes the problems of poor bonding ability and insufficient corrosion resistance of zinc-deposited aluminum alloy in the prior art. The chemical zinc deposition agent of the present invention comprises metal salts such as zinc salts and cobalt salts, a complexing agent, a stabilizer, an alkali and a mixed solvent. The deposited zinc-aluminum alloy is obtained by degreasing and alkali etching the aluminum alloy substrate, using the chemical zinc deposition agent for primary zinc deposition, zinc stripping, secondary zinc deposition, and washing; the zinc deposition rate is increased by controlling the amount of the complexing agent and the ratio of each component; the zinc deposition thickness is increased by adjusting the type and amount of the zinc salt; the bonding ability of the deposited zinc layer with the aluminum alloy substrate is improved by adjusting the type and amount of the cobalt salt, controlling the type and amount of the stabilizer; and the overall corrosion resistance of the deposited zinc-aluminum alloy is improved by adjusting the temperature, time and zinc deposition agent of the primary zinc deposition and the secondary zinc deposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of metal material surface treatment, in particular to an aluminum alloy chemical zinc deposition agent and a zinc deposition method. Background Art

[0002] Aluminum and aluminum alloys are widely used materials in industrial production and people's lives. Electroplating aluminum or aluminum alloys is an effective way to improve its electrical conductivity, thermal conductivity, weldability, and surface wear resistance, corrosion resistance, protection, decoration, and optical properties. Aluminum alloy products are very easy to be oxidized during the surface treatment process, which makes subsequent surface treatment more difficult. If you are not careful, it will cause blistering and peeling of the coating, resulting in a large number of quality problems.

[0003] The zinc immersion process before aluminum alloy electroplating (also known as aluminum zinc immersion) has gradually developed. Its main function is to remove the oxide film on the surface of aluminum or aluminum alloy, dissolve the exposed surface layer, and displace the zinc after dissolving the aluminum, so that the potential on the surface of the part becomes positive, improving the bonding strength between the substrate and the coating. Existing conventional aluminum alloy zinc immersion agents (zinc immersion solutions) all contain cyanide, but cyanide and HCN generated in the residual solution are highly toxic, which reduces safety during the subsequent electroplating or processing of aluminum alloys and increases the difficulty of process operation; cyanide-free zinc immersion has become the current trend, but acid zinc immersion is currently used in a very small range, and its effect and practicality are poor, so the cyanide-free zinc immersion process is mainly concentrated in alkaline zinc immersion.

[0004] The zinc immersion agent for aluminum alloy has developed from the original zinc-iron and zinc-nickel to the current zinc ion, nickel ion, copper ion, iron ion, cobalt ion and other multi-metal zinc immersion agents, which are more stable in performance and have a higher yield of aluminum alloy electroplating. Generally, the principle of alkaline zinc immersion is to reduce the activity of the aluminum surface by zinc immersion to prevent aluminum from being oxidized during operation or in the electroplating solution, and at the same time prevent the aluminum parts from undergoing a replacement reaction with the metal ions to be plated in the electroplating solution.

[0005] Patent CN110042374A discloses a chemical zinc deposition agent and zinc deposition method for aluminum alloy. The zinc deposition agent is prepared by limiting the weight of water-soluble zinc salt, water-soluble nickel salt, water-soluble copper salt, and water-soluble gluconate, and adding inorganic acid. The prepared zinc deposition agent is used to deposit zinc on aluminum alloy. The thickness of the zinc deposition layer is uniform, but the problem of poor bonding ability between the zinc deposition layer and the aluminum alloy substrate and poor corrosion resistance is not solved. At the same time, the invention uses an acid zinc immersion zinc deposition method, which reduces the practicality of the aluminum alloy.

[0006] In summary, in the prior art, in order to make the zinc-immersed layer denser, people add various additives to the basic zincate solution to improve the quality of the zinc-immersed layer. However, there is still a poor bonding ability between the zinc-immersed layer and the aluminum substrate, which affects the further use of the deposited zinc. At the same time, the zinc-immersed layer obtained by the zinc-immersed agent has poor corrosion resistance, which further limits the application scope of aluminum alloys.

[0007] Therefore, a chemical zinc deposition agent and a zinc deposition method for aluminum alloy are proposed. Summary of the invention

[0008] The invention aims to provide a chemical zinc precipitation agent and a zinc precipitation method for aluminum alloy, wherein the aluminum alloy substrate is degreased, alkaline-etched, and the chemical zinc precipitation agent is used to perform primary zinc precipitation, zinc stripping, and secondary zinc precipitation to obtain a deposited zinc aluminum alloy; the zinc precipitation rate is increased by controlling the dosage of the complexing agent and the dosage ratio of each component; the zinc deposition thickness is increased by adjusting the type and dosage of the zinc salt; the bonding ability of the deposited zinc layer with the aluminum alloy substrate is improved by adjusting the type and dosage of the cobalt salt and controlling the type and dosage of the stabilizer; the overall corrosion resistance of the deposited zinc aluminum alloy is improved by adjusting the temperature, time and zinc precipitation agent of the primary and secondary zinc precipitations; wherein the chemical zinc precipitation agent comprises zinc salt, cobalt salt, nickel acetate, copper acetate, ferric nitrate, complexing agent, stabilizer, alkali and mixed solvent.

[0009] To achieve the above object, the present invention provides the following technical solutions:

[0010] The present invention provides a chemical zinc precipitation agent for aluminum alloy, which comprises: 60-110 g / L zinc salt, 50 g / L nickel salt, 8 g / L copper salt, 5 g / L iron salt, 5-12 g / L cobalt salt, 30-50 g / L complexing agent, 10-18 g / L stabilizer, 120-160 g / L alkali compound, and the balance is a mixed solvent;

[0011] The mixed solvent is obtained by mixing methanol and water in a volume ratio of 1:9;

[0012] The complexing agent is selected from one or a mixture of two of sodium gluconate, disodium edetate, triethanolamine, tetrahydroxypropyl ethylenediamine, and sodium salicylate;

[0013] The stabilizer is selected from one of 3-amino-1,2,4-triazole, 2,2-bipyridine, and 2-mercaptobenzimidazole, or a mixture of two of them.

[0014] Preferably, the zinc salt is selected from zinc formate, zinc sulfate, zinc acetate, and zinc nitrate; and the alkali compound is selected from sodium hydroxide, lithium hydroxide, lithium acetate, and sodium acetate.

[0015] Preferably, the complexing agent is selected from a mixture of disodium ethylenediaminetetraacetate and tetrahydroxypropylethylenediamine; the concentration ratio of the disodium ethylenediaminetetraacetate to the tetrahydroxypropylethylenediamine is 1-7:1-7.

[0016] Preferably, the stabilizer is selected from a mixture of 3-amino-1,2,4-triazole and 2,2-bipyridine; the concentration ratio of the 3-amino-1,2,4-triazole to the 2,2-bipyridine is 1:1.

[0017] Preferably, the cobalt salt is selected from cobalt acetate and cobalt nitrate; the nickel salt is selected from nickel acetate; the copper salt is selected from copper acetate; and the iron salt is selected from iron nitrate.

[0018] A method for zinc deposition on an aluminum alloy, the method comprising the following steps:

[0019] S1. The aluminum alloy substrate is subjected to degreasing, alkaline etching, washing, and acid immersion to obtain a treated substrate;

[0020] S2. treating the treated substrate with a chemical zinc precipitation agent to obtain a primary zinc precipitation substrate;

[0021] S3 treating the primary zinc-precipitated substrate with a nitric acid solution to obtain a zinc-depleted substrate;

[0022] S4: subjecting the dezincified substrate to secondary zinc deposition using a chemical zinc deposition agent to obtain a secondary zinc deposition substrate; and washing the secondary zinc deposition substrate with deionized water to obtain a deposited zinc-aluminum alloy.

[0023] Preferably, the aluminum alloy is a commercially available aluminum alloy, including copper-aluminum alloy, aluminum-magnesium alloy, aluminum-silicon alloy, and aluminum-iron alloy, but not limited to the above alloys.

[0024] Preferably, the primary zinc precipitation treatment comprises the following steps: washing the treated substrate with deionized water, adding a chemical zinc precipitation agent to perform a primary zinc precipitation treatment to obtain a primary zinc precipitation substrate; wherein the zinc precipitation treatment temperature is 20-60°C; and the zinc precipitation treatment time is 40-80s.

[0025] Preferably, the chemical zinc precipitation agent includes 90-110 g / L zinc acetate, 50 g / L nickel acetate, 8 g / L copper acetate, 5 g / L ferric nitrate, 8 g / L cobalt acetate, 16 g / L disodium ethylenediaminetetraacetate, 24 g / L tetrahydroxypropylethylenediamine, 7.5 g / L 3-amino-1,2,4-triazole, 7.5 g / L 2,2-bipyridine, 150 g / L sodium hydroxide, and the balance is a mixed solvent.

[0026] Preferably, the secondary zinc deposition treatment includes the following steps: washing the stripped zinc substrate with deionized water, adding a second chemical zinc deposition agent for secondary zinc deposition treatment to obtain a secondary zinc deposition substrate; washing the secondary zinc deposition substrate with deionized water to obtain a deposited zinc-aluminum alloy; wherein the secondary zinc deposition temperature is 20-40°C, and the secondary zinc deposition time is 30-60s.

[0027] Preferably, the chemical zinc precipitation agent II includes 60-80 g / L zinc acetate, 50 g / L nickel acetate, 8 g / L copper acetate, 5 g / L ferric nitrate, 8 g / L cobalt acetate, 20 g / L disodium ethylenediaminetetraacetate, 20 g / L tetrahydroxypropylethylenediamine, 7.5 g / L 3-amino-1,2,4-triazole, 7.5 g / L 2,2-bipyridine, and 150 g / L lithium acetate, and the balance is a mixed solvent.

[0028] Compared with the prior art, the present invention has the following beneficial effects:

[0029] 1. The present invention uses disodium ethylenediaminetetraacetate and tetrahydroxypropylethylenediamine as a complexing agent, and uses the complexing agent to form a coordination bond with the metal ion, thereby "locking" the metal ion, reducing its activity in the reaction solution, and increasing the deposition rate; by controlling the amount of the complexing agent and the amount ratio of each component, the zinc deposition rate of the aluminum alloy substrate during the zinc deposition process is 17.25 μm / h, the deposition rate is improved, and the corrosion resistance of the aluminum alloy is improved.

[0030] 2. The present invention uses a zinc deposition agent prepared by adjusting the type and amount of zinc salt, the type and amount of alkali, and a mixed solvent of methanol and water. The thickness of the deposited zinc in the zinc deposition process of the aluminum alloy matrix is ​​0.068 μm, the thickness of the deposited zinc layer is increased, and the corrosion resistance of the aluminum alloy is improved.

[0031] 3. The present invention adjusts the type and amount of cobalt salt, controls the type and amount of stabilizer, utilizes cobalt ions to form a more compact and uniform structure with the zinc layer, and enhances the bonding force between the zinc layer and the substrate. At the same time, more nitrogen-containing group compounds are introduced to increase the adsorption and complexation with other metals, reduce the competitive complexation with zinc ions, and improve the bonding ability between the deposited zinc layer and the aluminum alloy substrate.

[0032] 4. The present invention further improves the corrosion resistance of the deposited zinc-aluminum alloy by controlling the primary zinc deposition temperature and time and adjusting the concentration ratio of the complexing agent components in the zinc deposition agent.

[0033] 5. The present invention selects zinc precipitators with different zinc salt concentrations and alkali types as zinc precipitators for the first zinc precipitation and the second zinc precipitation in the zinc precipitation process, respectively, and utilizes the fact that the binding force of lithium ions to water molecules is greater than that of sodium ions, thereby reducing the activity of hydroxide ions, forming a more compact and uniform structure of the zinc precipitation layer, and further improving the corrosion resistance under neutral and acidic conditions; by controlling the zinc precipitation rate and the thickness of the zinc precipitation layer in the two zinc precipitation processes, the overall corrosion resistance and binding force of the zinc-precipitated aluminum alloy are increased. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] Figure 1 The graph of the deposition rate of Examples 1-8 of the present invention as a function of the type of complexing agent;

[0035] Figure 2 This is a graph showing the variation of the zinc immersion layer thickness and deposition rate with the amount of zinc salt used in Example 19 and Examples 21-25 of the present invention. DETAILED DESCRIPTION

[0036] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0037] If the specific conditions are not specified in the examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. If the manufacturers of the reagents or instruments are not specified, they are all conventional products that can be purchased from the market.

[0038] See also Figure 1 to Figure 2 The present invention provides an aluminum alloy chemical zinc deposition agent and a zinc deposition method, and the technical scheme is as follows:

[0039] Example 1

[0040] Aluminum alloy chemical zinc deposition agent includes the following components:

[0041] 80 g / L zinc formate, 50 g / L nickel formate, 8 g / L copper formate, 5 g / L ferric nitrate, 40 g / L sodium gluconate, 15 g / L 3-amino-1,2,4-triazole, 8 g / L cobalt acetate, 150 g / L sodium hydroxide, and the remainder is a mixed solvent, wherein the mixed solvent is selected from methanol and water mixed in a volume ratio of 1:9.

[0042] The zinc deposition method of aluminum alloy comprises the following steps:

[0043] S1. Add the aluminum alloy substrate to an ultrasonic instrument and perform ultrasonic treatment at 60°C for 90 seconds to obtain an ultrasonic substrate; wash the treated substrate with deionized water, add it to a sodium hydroxide solution with a concentration of 40 g / L, and soak it at 60°C for 1 minute to obtain an alkaline-etched substrate; wash the alkaline-etched substrate with deionized water, add it to a hydrochloric acid solution with a concentration of 20 g / L, and soak it at 30°C for 1 minute to obtain a treated substrate;

[0044] S2: washing the treated substrate with deionized water, adding the aluminum alloy chemical zinc precipitation agent to perform a zinc precipitation treatment, the zinc precipitation temperature is 50° C., the zinc precipitation time is 60 seconds, and a primary zinc precipitation substrate is obtained;

[0045] S3. The zinc-deposited substrate is subjected to a nitric acid solution dezincification treatment at 30°C for 30s to obtain a zinc-dezincified substrate, wherein the nitric acid solution has a nitric acid mass concentration of 50%;

[0046] S4: Wash the stripped zinc substrate with deionized water, add it into the aluminum alloy chemical zinc precipitation agent for secondary zinc precipitation treatment, the zinc precipitation temperature is 30° C., the zinc precipitation time is 40 seconds, and a secondary zinc precipitation substrate is obtained; wash the secondary zinc precipitation substrate with deionized water to obtain a deposited zinc-aluminum alloy.

[0047] Example 2-15 The preparation method and parameter conditions are similar to those of Example 1, with the differences shown in Table 1.

[0048] Comparative Example 1 The preparation method and parameter conditions are the same as those of Example 1, except that no complexing agent is added to the aluminum alloy chemical zinc precipitation agent.

[0049] Example 16 Deposition rate determination

[0050] In the process of preparing the deposited zinc-aluminum alloy in Examples 1-15 and Comparative Example 1, the deposition rate in the first zinc deposition treatment was measured. The test method was calculated based on the increased weight of the aluminum alloy. The calculation formula is as follows:

[0051] γ=ΔM×10000 / ρ×s×t

[0052] Where γ is the deposition rate, μm / h; ΔM is the increase in the mass of the aluminum alloy substrate before and after, g; ρ is the specific gravity of the zinc layer, 7.14 g / cm 3 ; t is the deposition time, h; s is the area of ​​the aluminum alloy substrate; the test results are shown in Table 1; the deposition rate of Examples 1-8 varies with the type of complexing agent as shown Figure 1 shown.

[0053] Table 1 Deposition rate determination of Examples 1-15 and Comparative Example 1

[0054]

[0055] From the results in Table 1, it can be seen that in Comparative Example 1, the zinc deposition rate during the zinc deposition treatment without adding a complexing agent is significantly reduced compared with Examples 1-15. The too slow deposition rate prolongs the time for zinc to be deposited on the surface of the aluminum alloy. During the deposition process, due to the influence of metal ions and the environment, defects are generated in the zinc layer, which further affects the aluminum alloy electroplating process. At the same time, the rate is reduced, resulting in an extension of the zinc deposition time. The extension of time leads to further oxidation of aluminum on the surface of the aluminum alloy during the deposition process. Figure 1, Table 1 Examples 1-8 The results show that with the change of the type of complexing agent, the zinc deposition rate has obvious changes. The use of a single complexing agent has a significant rate improvement compared with Comparative Example 1. The complexing agent provides lone pairs of electrons in the zinc deposition process to form coordination bonds with metal ions, ensuring that the zinc ions can still be evenly dispersed in the solution in an alkaline environment without precipitation, thereby stabilizing the deposition liquid. At the same time, the complexing agent can form coordination bonds with metal ions in the solution with large bond energy, thereby "locking" the metal ions, reducing their activity in the reaction solution, and increasing the deposition rate; disodium ethylenediaminetetraacetic acid and tetrahydroxypropylethylenediamine are used to stably control the zinc ions in the complex system through covalent bonding between the complexing agents, increase the metal replacement of zinc ions with the aluminum alloy matrix, and increase the zinc deposition rate; Example 6, Example 9-11, with the increase in the amount of complexing agent used, the zinc deposition rate shows a trend of first increasing and then decreasing. With the increase in the amount of complexing agent used, the zinc deposition rate The deposition rate gradually accelerates, however, excessive complexing agent leads to increased complexing ability of zinc ions, reduced replacement with the surface of aluminum alloy, and decreased deposition rate; from the results of Example 6 and Examples 12-15, it can be seen that with the change of the complexing agent concentration ratio, the deposition rate changes significantly, with the increase of the dosage of disodium ethylenediaminetetraacetic acid, the reaction ability with tetrahydroxypropylethylenediamine is enhanced, the stability of the complex is increased, and a significantly increased zinc deposition rate is shown compared with a single complexing agent, however, zinc ions and tetrahydroxypropylethylenediamine show a stronger binding ability than the dosage of disodium ethylenediaminetetraacetic acid, the complexing degree of the complexing agent and zinc ions is increased, and the stability of the deposition solution is improved while increasing the zinc deposition rate; from the results of Table 1, it can be seen that disodium ethylenediaminetetraacetic acid and tetrahydroxypropylethylenediamine are used as composite complexing agents, and the dosage of each complexing agent is controlled at the same time, and the zinc deposition rate in the zinc deposition process of the aluminum alloy matrix is ​​17.25 μm / h, showing a significantly improved zinc deposition rate.

[0056] Examples 17-31 The preparation methods and parameter conditions of Example 12 are referred to, with the differences shown in Table 2.

[0057] Comparative Example 2 The preparation method and parameter conditions are the same as those of Example 12, except that water is used as the solvent for the zinc precipitation agent.

[0058] Comparative Example 3 The preparation method and parameter conditions are the same as those of Example 12, except that no alkali is used as the zinc precipitation agent.

[0059] Table 2 Component dosage of Examples 17-31

[0060]

[0061] Example 32 Determination of zinc immersion layer thickness

[0062] The thickness of the zinc-aluminum alloy prepared in Examples 17-31 and Comparative Examples 2-3 was subjected to zinc immersion treatment, and the deposition rate in the zinc immersion treatment was measured. The test method was the same as that described in Example 16. The test results are shown in Table 3. The thickness of the zinc immersion layer and the deposition rate of Examples 19 and 21-25 changed with the amount of zinc salt used as shown in Table 3. Figure 2 shown.

[0063] Table 3 Determination of zinc immersion layer thickness of Examples 17-31 and Comparative Examples 2-3

[0064]

[0065] It can be seen from the results in Table 3 that the thickness of the zinc-plated zinc-aluminum alloy obtained by using water as the solvent of the zinc-plating agent in Comparative Example 2 is significantly reduced compared with Examples 17-31, and the zinc deposition rate is reduced. The use of a mixed solvent of methanol and water improves the dispersibility of metal ions in the solution, and at the same time increases the complexing ability of the complexing agent and the metal ions, so that during the zinc deposition process, the zinc ions can still be uniformly dispersed in the solution in an alkaline environment without precipitation. At the same time, the addition of methanol improves the solubility of zinc acetate; It can be seen from the results of Examples 17-20 that zinc acetate is more soluble in the mixed solvent, and the free zinc ions are more stable in complexing with the complexing agent due to the stronger binding ability of acetate ions and sodium ions, which further improves the zinc deposition rate and the thickness of the zinc-plated zinc layer; Through Examples 19, Examples 21-25, Figure 2The results show that with the increase of zinc salt dosage, the deposition rate gradually increases, and the thickness of the zinc deposition layer gradually increases; when the zinc salt concentration is low, the zinc deposition layer is thinner, and under this condition, more time and energy will be consumed. With the increase of zinc salt concentration, the deposition layer appears coarse and discontinuous blocks, and some areas are seriously clustered, resulting in serious surface unevenness and increased surface tension. The thickness of the zinc deposition layer is increased, but it will affect the bonding strength and corrosion resistance of the zinc deposition layer. At the same time, if the chemical plating speed is too fast, the surface quality of the coating will drop sharply, and a dense zinc deposition layer cannot be formed. The results of Example 19 and Examples 26-28 show that with the change of the type of alkali, the thickness of the zinc deposition layer changes significantly. Compared with sodium ions, lithium ions have weaker alkalinity and a greater ability to bind water molecules than sodium ions, which reduces the activity of hydroxide ions. degree, inhibiting the dissolution and replacement reaction of the aluminum alloy, showing a decrease in hydroxide ions around the zinc ions on the surface of the substrate, a decrease in the dissolution of aluminum, a slower deposition of zinc, a more uniform discharge, and a thinner zinc layer; the results of Examples 19 and 29-31 show that the change in the amount of alkali has little effect on the thickness of the zinc deposition layer. The results of Comparative Example 3 show that not adding alkali solution has a significant effect on the formation of the zinc deposition layer during the zinc deposition process of the zinc deposition agent, the complexing of zinc ions is reduced, and the content of zinc replaced is reduced, showing a thin zinc deposition layer; the results of Table 3 show that by using zinc acetate as the zinc salt, adjusting the amount of zinc salt, controlling the type and amount of alkali, the thickness of the deposited zinc in the zinc deposition process of the obtained aluminum alloy substrate is 0.068 μm, showing a significantly increased thickness of the deposited zinc layer.

[0066] Examples 33-44 refer to the preparation method and parameter conditions of Example 19, and the differences are shown in Table 4.

[0067] Table 4 Parameter changes of Examples 33-44

[0068]

[0069] Comparative Example 4 The preparation method and parameter conditions are the same as those of Example 19, except that no cobalt salt is added.

[0070] Comparative Example 5 The preparation method and parameter conditions are the same as those of Example 19, except that no stabilizer is added.

[0071] Example 45 Binding Strength Test

[0072] The nickel layer was electroplated on the deposited zinc-aluminum alloy obtained in Examples 33-44 and Comparative Examples 4-5, and the bonding strength of the deposited layer was tested. The deposited layer was scratched with a sharp tool and then pried at the scratches with a blade to observe the state of the deposited layer. The results are shown in Table 5. The plating solution formula of the electroplated nickel layer is: NiSO4·7H2O 150g / L, MgSO4·7H2O 15g / L, sodium citrate dihydrate 200g / L, NaCl 12g / L, H3BO325g / L. The process parameters are: pH 6.2-7.0, temperature 40°C, time 1h, current density 3.2A / dm 2 .

[0073] Table 5 Binding strength test of Examples 33-44 and Comparative Examples 4-5

[0074]

[0075] The results in Table 5 show that the bonding ability of the deposited zinc-aluminum alloy obtained by not adding cobalt salt in Comparative Example 4 and not adding stabilizer in Comparative Example 5 with the aluminum alloy substrate is significantly reduced compared with Examples 33-44. The state of the zinc deposited layer observed by the scratch method obviously has peeling and shedding phenomena. Since the cobalt ions can form a more dense and uniform structure with the zinc layer, the bonding force between the zinc layer and the substrate is enhanced, thereby improving the adhesion and corrosion resistance of the zinc layer. At the same time, the addition of the stabilizer can adsorb and complex other ions in the zinc immersion solution, which loses catalytic activity during the zinc deposition process, increasing the bonding between the zinc deposition layer and the aluminum The bonding ability of the zinc deposition layer to the aluminum alloy substrate; the results of Examples 33-34 show that the addition of cobalt acetate has better solubility and dispersibility than the mixed solvent of cobalt nitrate in the zinc deposition agent, making it easier for the zinc immersion solution to wet and spread on the substrate surface, thereby allowing the zinc deposition replacement reaction to proceed smoothly, thereby increasing the zinc deposition rate and improving the bonding ability of the zinc deposition layer to the aluminum alloy substrate; the results of Examples 33 and 35-38 show that with the increase in the amount of cobalt salt used, the bonding ability of the zinc deposition layer to the aluminum alloy substrate shows a trend of first increasing and then decreasing. The use of excessive cobalt salt will affect the metal ion balance of the zinc deposition agent, It competitively combines with the complexing agent in the zinc deposition agent to reduce the generation of zinc complexes. During the deposition process, the zinc complex is reduced, which reduces the deposition rate. The thickness of the zinc deposition layer becomes thinner within the same time range, further reducing the binding ability of the zinc deposition layer with the aluminum substrate. The results of Examples 33 and 39-41 show that compared with the zinc deposition agent prepared using a single stabilizer, the stabilizer combination obtained by using 3-amino-1,2,4-triazole and 2,2-bipyridine in a concentration ratio of 1:1 has significantly improved binding ability. The introduction of 2,2-bipyridine introduces more nitrogen-containing group compounds, and the nitrogen-containing The compound can increase the adsorption and complexation with other metals, reduce the competitive complexation with zinc ions, increase the thickness of the zinc-plated layer, and improve the bonding ability; the results of Examples 41-44 show that with the change of the amount of stabilizer, the effect on the bonding force between the zinc-plated layer and the aluminum alloy substrate is small; the results of Table 5 show that by controlling the amount of cobalt acetate, using 3-amino-1,2,4-triazole and 2,2-bipyridine as stabilizers, and controlling the amount of stabilizer, the deposited zinc-aluminum alloy obtained has no peeling at the intersection of the zinc-plated layer observed by the scratch method, and the coating does not fall off after prying, and there is no warping, showing a significantly improved bonding ability.

[0076] Embodiment 46

[0077] Aluminum alloy chemical zinc deposition agent includes the following components:

[0078] 80g / L zinc acetate, 50g / L nickel acetate, 8g / L copper acetate, 5g / L ferric nitrate, 8g / L cobalt acetate, 20g / L disodium ethylenediaminetetraacetate, 20g / L tetrahydroxypropylethylenediamine, 7.5g / L 3-amino-1,2,4-triazole, 7.5g / L 2,2-bipyridine, 150g / L sodium hydroxide, and the remainder is a mixed solvent, wherein the mixed solvent is obtained by mixing methanol and water in a volume ratio of 1:9.

[0079] The zinc deposition method of aluminum alloy comprises the following steps:

[0080] S1. Add the aluminum alloy substrate to an ultrasonic instrument and perform ultrasonic treatment at 60°C for 90 seconds to obtain an ultrasonic substrate; wash the treated substrate with deionized water, add it to a sodium hydroxide solution with a concentration of 40 g / L, and soak it at 60°C for 1 minute to obtain an alkaline-etched substrate; wash the alkaline-etched substrate with deionized water, add it to a hydrochloric acid solution with a concentration of 20 g / L, and soak it at 30°C for 1 minute to obtain a treated substrate;

[0081] S2: washing the treated substrate with deionized water, adding the aluminum alloy chemical zinc precipitation agent to perform a zinc precipitation treatment, the zinc precipitation temperature is 50° C., the zinc precipitation time is 60 seconds, and a primary zinc precipitation substrate is obtained;

[0082] S3. The zinc-deposited substrate is subjected to a nitric acid solution dezincification treatment at 30°C for 30s to obtain a zinc-dezincified substrate, wherein the nitric acid solution has a nitric acid mass concentration of 50%;

[0083] S4: Wash the treated substrate with deionized water, add it into the aluminum alloy chemical zinc precipitation agent for secondary zinc precipitation treatment, the zinc precipitation temperature is 30°C, the zinc precipitation time is 40s, and a secondary zinc precipitation substrate is obtained; wash the secondary zinc precipitation substrate with deionized water to obtain a deposited zinc-aluminum alloy.

[0084] Examples 47-56 Refer to the preparation method and parameter conditions of Example 46, with the differences shown in Table 6.

[0085] Comparative Example 6 The preparation method and parameter conditions are the same as those of Example 46, except that no zinc removal treatment is performed.

[0086] Example 57 Corrosion resistance test

[0087] The deposited zinc-aluminum alloys prepared in Examples 46-56 and Comparative Example 6 were immersed in an aqueous solution of 5% sodium chloride and placed at 30°C for 10 days. The corrosion rate of the deposited zinc-aluminum alloy was determined by the change in mass before and after. The results of the neutral corrosion rate are shown in Table 6. The deposited zinc-aluminum alloys were immersed in an aqueous solution of 5% (mass fraction) boric acid solution and placed at 30°C for 10 days. The corrosion rate of the deposited zinc-aluminum alloy was determined by the change in mass before and after. The results of the acidic corrosion rate are shown in Table 6.

[0088] Table 6 Corrosion rate determination of Examples 46-56 and Comparative Example 6

[0089]

[0090] From the results in Table 6, it can be seen that the corrosion rate of the deposited zinc-aluminum alloy under neutral conditions and acidic conditions obtained in Comparative Example 6 without zinc stripping treatment is significantly improved compared with Examples 46-56, and the corrosion resistance is poor. In the zinc stripping process, on the one hand, the impurity metals remaining on the surface of the aluminum alloy can be removed, and on the other hand, the zinc elements with poor bonding strength and loose deposition in the zinc deposition layer can be consumed by reaction, thereby reducing the impact on the corrosion performance; From the results in Examples 46-50, it can be seen that with the change in the concentration ratio of the complexing agent mixture, the corrosion resistance of the deposited zinc-aluminum alloy changes significantly due to the change in the deposition rate. With the increase in the deposition rate, the thickness of the formed zinc deposition layer increases, reducing the neutral corrosion rate. However, the continuous increase in the thickness of the zinc deposition layer will cause the deposited zinc layer to weaken due to the weakening of the bonding strength and the reduction of the zinc complex during the secondary zinc deposition process, so that the density of the deposited zinc is gradually weakened. Under acidic conditions, due to the corrosion of hydrogen ions on zinc, the zinc deposition layer is gradually consumed, further reducing the corrosion resistance of the aluminum alloy; The results of Examples 47 and 51-56 can be It is known that with the increase of the primary zinc deposition temperature, the corrosion resistance of the aluminum alloy gradually increases. The higher the temperature, the more violent the molecular movement, migration and diffusion. The enhanced effective collision between molecules accelerates the zinc deposition, but the too fast zinc deposition speed will reduce the density of the zinc deposition layer. At the same time, the too high deposition temperature will cause the accumulation of zinc atoms in some abrupt areas on the surface of the zinc deposition layer. These accumulations cause stress concentration areas on the surface of the coating, reducing the bonding force and corrosion resistance of the zinc deposition layer. Similarly, with the extension of time, the too fast zinc deposition rate leads to the rapid accumulation of the zinc deposition thickness, further affecting the density of the zinc layer and reducing the corrosion resistance. In summary, it is necessary to use the zinc deposition agent used in the primary zinc deposition process and the secondary zinc deposition process separately. The primary zinc deposition process requires the rapid deposition of complex zinc to increase the thickness of the zinc deposition layer. The secondary zinc deposition process requires a slow zinc deposition rate to reduce the rapid accumulation of the zinc layer thickness, so as to use the auxiliary metal ions to control the growth of zinc atom grains, avoid the decrease in density caused by rapid accumulation, maintain the thickness of the zinc deposition layer while improving the density, and further improve the corrosion resistance of the zinc deposition aluminum alloy.

[0091] Embodiment 58

[0092] The primary aluminum alloy chemical zinc deposition agent includes the following components:

[0093] 90g / L zinc acetate, 50g / L nickel acetate, 8g / L copper acetate, 5g / L ferric nitrate, 8g / L cobalt acetate, 16g / L disodium ethylenediaminetetraacetate, 24g / L tetrahydroxypropylethylenediamine, 7.5g / L 3-amino-1,2,4-triazole, 7.5g / L 2,2-bipyridine, 150g / L sodium hydroxide, and the remainder is a mixed solvent, which is selected from methanol and water mixed in a volume ratio of 1:9.

[0094] Secondary aluminum alloy chemical zinc deposition agent includes the following components:

[0095] 60g / L zinc acetate, 50g / L nickel acetate, 8g / L copper acetate, 5g / L ferric nitrate, 8g / L cobalt acetate, 20g / L disodium ethylenediaminetetraacetate, 20g / L tetrahydroxypropylethylenediamine, 7.5g / L 3-amino-1,2,4-triazole, 7.5g / L 2,2-bipyridine, 150g / L lithium acetate, and the remainder is a mixed solvent, wherein the mixed solvent is obtained by mixing methanol and water in a volume ratio of 1:9.

[0096] The zinc deposition method of aluminum alloy comprises the following steps:

[0097] S1. Add the aluminum alloy substrate to an ultrasonic instrument and perform ultrasonic treatment at 60°C for 90 seconds to obtain an ultrasonic substrate; wash the treated substrate with deionized water, add it to a sodium hydroxide solution with a concentration of 40 g / L, and soak it at 60°C for 1 minute to obtain an alkaline-etched substrate; wash the alkaline-etched substrate with deionized water, add it to a hydrochloric acid solution with a concentration of 20 g / L, and soak it at 30°C for 1 minute to obtain a treated substrate;

[0098] S2: washing the treated substrate with deionized water, adding the aluminum alloy chemical zinc precipitation agent to perform a zinc precipitation treatment, the zinc precipitation temperature is 50° C., the zinc precipitation time is 60 seconds, and a primary zinc precipitation substrate is obtained;

[0099] S3. The zinc-deposited substrate is subjected to a nitric acid solution dezincification treatment at 30°C for 30s to obtain a zinc-dezincified substrate, wherein the nitric acid solution has a nitric acid mass concentration of 50%;

[0100] S4: Wash the stripped zinc substrate with deionized water, add it into the aluminum alloy chemical zinc precipitation agent for secondary zinc precipitation treatment, the zinc precipitation temperature is 30° C., the zinc precipitation time is 40 seconds, and a secondary zinc precipitation substrate is obtained; wash the secondary zinc precipitation substrate with deionized water to obtain a deposited zinc-aluminum alloy.

[0101] Examples 59-67 Refer to the preparation method and parameter conditions of Example 58, as shown in Table 7.

[0102] Table 7 Parameter changes of Examples 58-67

[0103]

[0104] Example 68 Corrosion resistance test

[0105] The deposited zinc-aluminum alloys prepared in Examples 58-67 were immersed in an aqueous solution of 5% sodium chloride and placed at 30°C for 10 days. The corrosion rate of the deposited zinc-aluminum alloys was determined by the change in mass before and after. The results of neutral corrosion rate are shown in Table 8; the deposited zinc-aluminum alloys were immersed in an aqueous solution of 5% (mass fraction) boric acid solution and placed at 30°C for 10 days. The corrosion rate of the deposited zinc-aluminum alloys was determined by the change in mass before and after. The results of acidic corrosion rate are shown in Table 8. The deposited zinc-aluminum alloys obtained in Example 47 without separate use of the zinc deposition agent were used as a comparison.

[0106] Table 8 Corrosion resistance test of Example 47, Example 58-67

[0107]

[0108] The results in Table 8 show that the corrosion rate under neutral conditions and the corrosion rate under acidic conditions of the deposited zinc-aluminum alloy obtained by using zinc precipitators with different zinc salt concentrations for primary and secondary zinc precipitation are significantly reduced compared to Example 47 without zinc precipitation, showing significantly improved corrosion resistance. The results of Examples 58-62 show that with the increase of zinc acetate concentration in the primary zinc precipitator, the zinc deposition rate increases, showing a significantly improved zinc deposition layer thickness and improved corrosion resistance. At the same time, the concentration in the secondary zinc precipitator decreases, and the alkalinity of lithium acetate is weak, which avoids the rapid accumulation of the zinc deposition layer thickness. At the same time, the binding force of lithium ions to water molecules is greater than that of sodium ions, which reduces the activity of hydroxide ions and inhibits the dissolution and replacement reaction of aluminum. In the secondary zinc precipitation process, the zinc deposition is more The introduction of cobalt ions is slow, and a denser and more uniform structure is formed with the zinc layer. The obtained zinc-immersed layer is thinner, but the density is greatly improved, the corrosion resistance is increased, and the rapid corrosion under acidic conditions is avoided; the results of Example 60 and Examples 63-64 show that excessive increase in temperature will increase the zinc deposition rate in the secondary zinc deposition process, the formation of a dense structure is limited, and the corrosion resistance is reduced; the results of Examples 60 and Examples 65-67 show that with the extension of deposition time, the corrosion resistance of the aluminum alloy gradually improves, but too long a time will further affect the bonding strength between the deposited zinc layer and the aluminum alloy substrate; in summary, by controlling the type of zinc deposition agent in the first zinc deposition process and the type of zinc deposition agent in the second zinc deposition process, and adjusting the temperature and time of the secondary zinc deposition, the deposited zinc-aluminum alloy obtained has significantly improved corrosion resistance.

[0109] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A chemical zinc deposition agent for aluminum alloy, characterized in that: The chemical zinc precipitation agent comprises: 60-110 g / L zinc salt, 50 g / L nickel salt, 8 g / L copper salt, 5 g / L iron salt, 5-12 g / L cobalt salt, 30-50 g / L complexing agent, 10-18 g / L stabilizer, 120-160 g / L alkali compound, and the balance is a mixed solvent; The mixed solvent is obtained by mixing methanol and water in a volume ratio of 1:9; The zinc salt is zinc acetate; the alkali compound is selected from one of sodium hydroxide and lithium acetate; The complexing agent is a mixture of disodium ethylenediaminetetraacetate and tetrahydroxypropylethylenediamine; the concentration ratio of the disodium ethylenediaminetetraacetate to the tetrahydroxypropylethylenediamine is 1-7:1-7; The stabilizer is a mixture of 3-amino-1,2,4-triazole and 2,2-bipyridine; the concentration ratio of the 3-amino-1,2,4-triazole to the 2,2-bipyridine is 1:1; The cobalt salt is selected from cobalt acetate; the nickel salt is selected from nickel acetate; the copper salt is selected from copper acetate; and the iron salt is selected from iron nitrate.

2. A zinc deposition method for aluminum alloy, characterized in that: The zinc precipitation method comprises the following steps: S1. The aluminum alloy substrate is subjected to degreasing, alkaline etching, washing, and acid immersion to obtain a treated substrate; S2. treating the treated substrate with a chemical zinc precipitation agent to obtain a primary zinc precipitation substrate; S3 treating the primary zinc-precipitated substrate with a nitric acid solution to obtain a zinc-depleted substrate; S4: treating the dezincified substrate with a chemical zincating agent for secondary zinc deposition to obtain a secondary zinc deposition substrate; washing the secondary zinc deposition substrate with deionized water to obtain a deposited zinc-aluminum alloy; The primary zinc precipitation treatment comprises the following steps: washing the treated substrate with deionized water, adding a chemical zinc precipitation agent to perform a primary zinc precipitation treatment, and obtaining a primary zinc precipitation substrate; wherein the zinc precipitation treatment temperature is 50° C.; and the zinc precipitation treatment time is 60 seconds; The chemical zinc precipitation agent 1 includes 110g / L zinc acetate, 50g / L nickel acetate, 8g / L copper acetate, 5g / L ferric nitrate, 8g / L cobalt acetate, 16g / L disodium ethylenediaminetetraacetate, 24g / L tetrahydroxypropylethylenediamine, 7.5g / L 3-amino-1,2,4-triazole, 7.5g / L 2,2-bipyridine, 150g / L sodium hydroxide, and the balance is a mixed solvent; The secondary zinc deposition treatment comprises the following steps: washing the zinc-stripped substrate with deionized water, adding a second chemical zinc deposition agent for secondary zinc deposition treatment to obtain a secondary zinc deposition substrate; washing the secondary zinc deposition substrate with deionized water to obtain a deposited zinc-aluminum alloy; wherein the secondary zinc deposition temperature is 30° C., and the secondary zinc deposition time is 40 seconds; The chemical zinc precipitation agent II comprises 60 g / L zinc acetate, 50 g / L nickel acetate, 8 g / L copper acetate, 5 g / L ferric nitrate, 8 g / L cobalt acetate, 20 g / L disodium ethylenediaminetetraacetate, 20 g / L tetrahydroxypropylethylenediamine, 7.5 g / L 3-amino-1,2,4-triazole, 7.5 g / L 2,2-bipyridine, 150 g / L lithium acetate, and the balance is a mixed solvent; The chemical zinc precipitation agent is obtained as claimed in claim 1.

Citation Information

Patent Citations

  • Aluminum alloy chemical zinc precipitating agent and zinc precipitating method

    CN110042374A

  • Non-cyanide zinc-deposited solution and non-cyanide plating method of aluminum wheel boss using non-cyanide zinc-deposited solution

    CN101580952A

  • Cyanide-free zinc dipping solution and cyanide-free electroplating method of filter aluminium alloy by using the same

    CN102732922A

  • Chemical copper plating solution and method for plating copper substrate by using chemical copper plating solution

    CN113388829A